IMPLEMENTATION OF QUANTITATIVE STRATEGIC PLANNING MATRIX (QSPM) IN A DIGITAL-BASED PROMOTION STRATEGY AT A MUSLIM CLOTHING STORE IN PADANGSIDIMPUAN CITY - Hery Dia Anata Batubara (Jurnal Ekonomi, 2022)
Indonesia is currently being hit by a problem, namely the problem of the Covid-19 pandemic. The huge impact arising from this pandemic is very much felt in various factors. From a health perspective, as of October 20, 2020, there were more than 290,000 confirmed cases of COVID-19. From an economic perspective, the COVID-19 pandemic has an impact on economic growth. Indonesia's economy in the first quarter of 2020 against the first quarter of 2019 was 2.97% (y-on-y), slowing down compared to the achievement in the first quarter of 2019 of 5.07%. (BPS Republic of Indonesia). In the production perspective, the number of production units decreased drastically due to the inability to maintain their production units which also had an impact on increasing the number of layoffs and unemployment, especially in production units in traditional markets which in fact have a slow economic growth rate coupled with the increasing number of competitors. This makes Indonesia in a dilemmatic position. Handling Problems to increase economic growth, the Indonesian government echoed the "New Normal Era" and began to live in peace with Covid-19 until an effective vaccine was found. All units of production activities are now starting to return to increase their economic growth by increasing their sales. This New Normal era is unfamiliar to all levels of society because it has to fight and strengthen new strategies in order to improve its economy. One of the production activity units that are now struggling to implement strategies in order to increase economic growth is traditional shops by implementing targeted marketing strategies so that they are able to compete and increase economic growth during the Covid-19 pandemic because there is more competition and people's purchasing power is declining. The research was conducted at 2 Muslim Clothing Stores located in the Sangkumpal Bonang Padangsidimpuan Traditional Market. The purpose of this study is to implement marketing strategies that are right on target and able to compete in the era of the Covid-19 pandemic. Analytical methods in this study use quantitative methods and qualitative methods. The quantitative method is carried out by providing a list of questionnaires to the three research objects related to the impact felt during the Covid-19 pandemic while the qualitative method is carried out by applying marketing strategies that are right on target. As well as the use of the QSPM (Quantitative Strategic Planning Matrix) method as a digital-based promotion strategy.